2005
DOI: 10.1093/chemse/bji051
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Concentrations of Orally Administered Flavors

Abstract: The odorants emanating from the oral cavity during eating and drinking reach the olfactory mucosa via the pharynx (retronasal olfaction). It is unclear which variables influence the perception of intraorally applied substances. The aim of the present study was to determine the temporal profiles of volatile odor concentrations at different locations in the nasal cavity during consumption of liquid and solid custard samples using proton transfer reaction mass spectrometry. Intranasal odor concentrations were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Orthonasally and retronasally delivered odorants both activate the same olfactory epithelium at the top of the nasal cavity. However, they reach it from different directions and may, hence, activate different zones of the olfactory epithelium (Ressler et al 1993) in a different order (Frasnelli et al 2005), which would result in Fig. 2 Mean hedonic ratings (error bars indicate standard error of mean) in estimation units (EU) for ten food odors (left) and ten nonfood odors (right) after orthonasal (filled bars) and retronasal (open bars) presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Orthonasally and retronasally delivered odorants both activate the same olfactory epithelium at the top of the nasal cavity. However, they reach it from different directions and may, hence, activate different zones of the olfactory epithelium (Ressler et al 1993) in a different order (Frasnelli et al 2005), which would result in Fig. 2 Mean hedonic ratings (error bars indicate standard error of mean) in estimation units (EU) for ten food odors (left) and ten nonfood odors (right) after orthonasal (filled bars) and retronasal (open bars) presentation.…”
Section: Discussionmentioning
confidence: 99%
“…One study that sought to quantify temporal and spatial differences in retronasal olfactory profiles given different textured custards (liquid vs solid custard) showed that the volatiles reached the olfactory epithelium at different times and positions depending on the food stimulus. 3 Another study showed that older individuals preferred a higher level of oral irritation in some foods but were less able to discriminate texture in foods than do younger adults. 71 Clearly, how we perceive the flavor of our food and determining what we like to eat is very complex.…”
Section: Chemesthesis and Agingmentioning
confidence: 99%
“…2 In addition, pureed food eliminates the need to chew, which breaks down food textures and increases the availability of flavor. 3 However, it may also not taste right because of changes in the patient's own sensory system. Taste and smell are known in the field of sensory science as the chemosenses (chemical senses) because they are stimulated by a chemical reaction.…”
mentioning
confidence: 99%
“…These analytical techniques have been used to reveal the relationship between the intensity of the aroma perceptions and the aroma release during the consumption of foods and drinks (Gwartney et al, 2000;Hollowood et al, 2000;Lethuaut et al, 2004;Linforth et al, 1999;Mestres et al, 2005;Saint-Eve et al, 2009;Weel et al, 2002). In addition, Beauchamp et al and Fransnelli et al also developed other analytical techniques capable of analyzing the odorants passing through the nasopharynx and reaching the olfactory epithelium in order to understand the in-mouth release in more detail (Beauchamp et al, 2014;Frasnelli et al, 2005).Coffee is widely appreciated for its characteristic aroma and T. Itobe et al 608 taste, and is often enjoyed with milk or creamer. The purposes of adding these products to coffee are to develop a desirable color change, to reduce the bitter and sour tastes, and to reduce the astringency of coffee.…”
mentioning
confidence: 99%